Tissue-specific biosynthesis and regulation of alkaloids, flavonoids, and terpenoids in fenugreek (Trigonella foenum-graecum L.): insights from integrated metabolomics and transcriptomics analysis - Dong, Shiqing; Han, Xiaokang; Man, Xiuyuan; Deng, Xiangmin; Chen, Zinuo (Frontiers in Plant Science, 2025)
IntroductionFenugreek (Trigonella foenum-graecum L.) is a medicinal and edible plant containing bioactive compounds with therapeutic potential. However, the tissue-specific distribution and biosynthetic pathways of these compounds remain poorly characterized.MethodsThis study employed metabolomics and transcriptomics to analyze metabolite profiles and gene expression in fenugreek roots, stems, and leaves. Using UPLC-MS/MS, we identified 2,124 metabolites, and full-length transcriptome sequencing alongside RNA-seq analysis revealed tissue-specific differentially expressed genes (DEGs).ResultsOur analysis revealed distinct tissue-specific accumulation patterns of alkaloids, flavonoids, and terpenoids. The roots were identified as the primary site for the biosynthesis of these secondary metabolites. Multi-omics integration pinpointed key biosynthetic genes, such as cytochrome P450s (CYP450s) and chalcone synthase (CHS). Furthermore, integrated co-expression networks and molecular docking simulations indicated functional associations between ABC transporters and bioactive compounds. Transcriptional regulation analysis suggested MYB and bHLH transcription factors as potential modulators of metabolic biosynthesis.DiscussionThis study enhances understanding of metabolic regulations in fenugreek and offers molecular resources for medicinal plant breeding.